Implementasi Digitalisasi UMKM di Kabupaten Boyolali Melalui Pelatihan Pemasaran Online - Myra Andriana; Tantik Sumarlin; Sindhu Rakasiswi; Nining Fitriani; Dwi Setiawan; Yuli Fitrianto; Gibson Manalu; Ayyub Hamdanu Budi Nurmana (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Mojosongo Subdistrict, Boyolali District with material on implementing marketing strategies by optimizing Facebook social media and endorsements through local influencers which aim to increase sales and increase buyer visits. Influencers can create an increased brand image, are inexpensive in cost and have a level of popularity, ability, reputation, and expertise in endorsing a product or service. The presentation of the material was accompanied by hands-on practice and also given time for discussion and questions and answers between the presenters and participants in community service activities (PkM). This activity was carried out face to face which was enthusiastically attended by the owners and employees of the AJB food stall in Boyolali. Online marketing training activities involve a team of lecturers from the University of Science and Computer Technology (STEKOM) Semarang from various cross-disciplinary fields, such as information systems, graphic design, computerized accounting and informatics engineering. It is hoped that from the results of this training, MSME actors can continue to improve their skills in the field of online marketing.